Rapid evolution of silver nanoparticle resistance in Escherichia coli - Graves, Joseph L.; Tajkarimi, Mehrdad; Cunningham, Quincy; Campbell, Adero; Nonga, Herve; Harrison, Scott H.; Barrick, Jeffrey E. (Frontiers in Genetics, 2015)
The recent exponential increase in the use of engineered nanoparticles (eNPs) means both greater intentional and unintentional exposure of eNPs to microbes. Intentional use includes the use of eNPs as biocides. Unintentional exposure results from the fact that eNPs are included in a variety of commercial products (paints, sunscreens, cosmetics). Many of these eNPs are composed of heavy metals or metal oxides such as silver, gold, zinc, titanium dioxide, and zinc oxide. It is thought that since metallic/metallic oxide NPs impact so many aspects of bacterial physiology that it will difficult for bacteria to evolve resistance to them. This study utilized laboratory experimental evolution to evolve silver nanoparticle (AgNP) resistance in the bacterium Escherichia coli (K12 MG1655), a bacterium that did not harbor any silver resistance elements. After 225 generations of exposure to the AgNP environment, the treatment populations demonstrated greater fitness versus control strains as measured by optical density (OD) and colony forming units (CFU) in the presence of varying concentrations of 10nm citrate-coated silver nanoparticles (AgNP) or silver nitrate (AgNO3). Genomic analysis shows that changes associated with AgNP resistance were already accumulating within the treatment populations by generation 100, and by generation 200 three mutations had swept to high frequency in the AgNP resistance stocks. This study indicates that despite previous claims to the contrary bacteria can easily evolve resistance to AgNPs, and this occurs by relatively simple genomic changes. These results indicate that care should be taken with regards to the use of eNPs as biocides as well as with regards to unintentional exposure of microbial communities to eNPs in waste products.